Numerical algorithm for the computation of compressible turbulent flows at arbitrary Mach number regimes - Ong, Kian Chuan (2017)
Mach-uniform algorithms are unified numerical algorithms for the computation of fluid flows at arbitrary Mach number regimes. These methods are important for practical engineering applications that involve both compressible and incompressible fluid flows together, such as shock wave/boundary layer interactions and cavitating fluid flows. In the present study, a pressure-based Mach-uniform algorithm is formulated to solve viscous fluid flows at arbitrary Mach number regimes encompassing subsonic, transonic, supersonic and hypersonic, in an accurate, robust and flexible manner. The core concept is based upon a hybrid integration of pressure-based algorithm and Simple Low-dissipation Advection Upstream Splitting Method II (SLAU2).